CCK-2/Gastrin-R Immunodistribution in a Solid Pseudopapillary Pancreatic Tumor: A Case Report of a 28-Years-Old North African Woman - Noria Harir; Feriel Sellam; Nesrine M Mrabent; Abdenacer Tou; Houria Belkralladi; Rachida Salah; Soumia Zeggai (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2016)
The presence of a large bulky pancreatic tumour in a young female should raise suspicions of the diagnosis of solid-pseduopapillary tumour of the pancreas. Solid pseudopapillary neoplasms of the pancreas are uncommon, accounting for only 1-2% of all pancreatic neoplasms. These tumors are being detected at an increased rate, probably due to the increased awareness and the liberal use of imaging. We report a case of a 28-year-old North African woman with no prior medical or surgical history diagnosed with solid pseudopapillary pancreatic tumor. Our immunohistochemical study demonstrated that the tumor cells were positive for CCK-2/gastrin receptors and that were highly expressed within the cytoplasmic area of the cells. Hence we attempted to raise a hypothesis and to establish a link between some female hormones which represents powerful regulators of the expression of CCK and their possible impact on the development of solid pseudopapillary pancreatic tumours in young women.